COOKING OIL SCARCITY PHENOMENON IN INDONESIA IN 2022 - Irmanelly Irmanelly; Ardi Afrizal; Trie Hierdawati; Amrizal Amrizal; Dani Dani (Universitas Dharma Wacana, 2022)
The purpose of this study is to describe the phenomenon of scarcity of cooking oil supply in Indonesia in 2022 using a descriptive analysis model through published data where the findings of this study are the cause of the scarcity of Indonesian cooking oil supply in general, due to producers experiencing a decline in marketing cooking oil in the country, the price of CPO in Indonesia. the world market is experiencing price increases, the B30 Program is a government program to make it mandatory to mix 30 percent diesel with 70 percent diesel fuel. There is a shift towards biodiesel production. The third factor is the unfinished condition of the Covid-19 pandemic So that the right solution to overcome the scarcity of cooking oil is to maintain the stability of CPO production and the prevailing pricing mechanism and by strengthening the role of BULOG